Effect Of Work Pressure on Job Satisfaction Levels Among Physiotherapists In Uttar Pradesh - Sharma, Vikas; Zafar, Shahiduz (Journal of Neonatal Surgery, 2025)
Background: Physiotherapists are an integral part of the healthcare system, but they generally face a tremendous level of work pressure that affects their job satisfaction and work performance. This study explores the correlation between physiotherapists' work pressure and job satisfaction in Uttar Pradesh. Objective: To explore how factors such as years of experience, number of working hours per week, and number of patients per day influence job satisfaction levels among physiotherapists. Methods: A cross-sectional, quantitative research study was conducted on 302 physiotherapists practicing in various healthcare establishments in Uttar Pradesh. Data were collected through structured questionnaires and statistically analyzed to determine significance as well as correlations. Results: The findings pointed towards the fact that job satisfaction was highest in novice physiotherapists and in those who worked fewer hours with a moderate patient load. A significant negative correlation between working hours and job satisfaction was observed, and a non-linear correlation was observed between patient volume and satisfaction. Part-time working hours and moderate patient loads (21–30 patients/day) were positively associated with higher satisfaction (p < 0.001). Conclusion: Workload exerts a strong influence on job satisfaction in physiotherapists in Uttar Pradesh. Reducing high workloads and optimizing patient numbers by better scheduling and organizational support may improve professional well-being and quality of service. These findings can guide policymakers and health administrators in formulating policies to enhance job satisfaction and retention in the physiotherapy workforce.